The knowledge, awareness, attitude and motivational analysis of plastic waste and household perspective in Malaysia - Rafia, Afroz; Rahman, Mohammed Ataur; Masud, Muhammad Mehedi Ehedi; Akhtar, Rulia (Springer Science + Business Media, 2017)
The focus of this study is to analyze the level of knowledge, awareness, and attitude toward plastic waste and to distinguish the key drivers that encourage the households in Kuala Lumpur, Malaysia, to participate in “ No plastic campaign”. This study used the logistic regression model to explain the factors that may affect the willingness to participate (WTP) of households in the campaign. In this study, it is found that 35 % of households are willing to participate in the campaign. The results of the study also indicate that people who are more informed and more convinced of their knowledge have a more positive attitude toward recycling than their counterparts do. Furthermore, this study provides additional evidence of the level and classification of importance of motivating factors for plastic recycling, using the modified aver- age and coefficient of variation of the models. From the analysis, the factor “helps reduce landfill use” is found as the most important factor and the factor of Braising money for charity^ is found as the least important factor that motivates house- holds to participate in recycling. The determinations of the study suggest some strategies that could hold implications for government and households to boost them to participate in the campaign “No Plastic Bag”.